PENGARUH VARIASI SUHU PENYIMPANAN TERHADAP STABILITAS FISIK SUSPENSI AMOXICILLIN - Dewi Rashati, Mikhania C.E, Dewi Nisa (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2017)
This study aims to investigate effect of variation storage temperature on the physical stability of amoxicillin suspension. The physical stability of the amoxicillin suspension included organoleptic, pH, viscosity and volumes of flocculation and deflocculation sedimentation. The research method used true experimental design method with pre-test and post-test control group design. The sample used amoxicillin suspension with temperature storage variation were cold temperature, room temperature and warm temperature. The results of research data on physical stability of organoleptic were processed compared with the condition before storage. The results of research data on physical stability of pH, viscosity and volume of flocculation sedimentation were analyzed using One Way Annova. From the organoleptic suspension of amoxicillin there is significant difference. Data using SPSS with One Way Anova method. All samples at amoxicillin suspension pH with variation of storage temperature got significance value of p0,05, stability of pH has a difference. Viscosity of amoxicillin suspension with variation of storage temperature, the significance value of p0.05, the viscosity physical stability has a significant difference. In flocculation of amoxicillin suspension with variation of storage temperature, the significance value of p0.05 means flocculation in the has a significant difference. In this study the amoxicillin control suspension and all temperature storage did not occur deflocculation.Keywords: Physical stability, Amoxicillin, Suspension